2008
DOI: 10.1577/t07-228.1
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal Variation in Physiological and Behavioral Responses of Nest‐Guarding Smallmouth Bass to Common Recreational Angling Practices

Abstract: Abstract.-Management policies related to catch-and-release (CR) angling of smallmouth bass Micropterus dolomieu vary widely across the geographic distribution of the species. Some jurisdictions, principally in the northern latitudes, prohibit or limit angling efforts that target nesting male smallmouth bass, whereas angling during the nesting period is generally unregulated in southern jurisdictions. Existing studies of individuallevel angling impacts on nesting smallmouth bass have primarily been conducted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 33 publications
2
11
1
Order By: Relevance
“…Catch-and-release fish were removed from the nest for a much shorter duration than tournament fish and did not experience the increased stress of weigh-in and displacement from nesting location. The abandonment rate of catch-and-release fish in our study (32%) was higher than that observed in similar studies with largemouth bass (about 10%; Siepker et al 2009) and smallmouth bass (0-10%; Suski et al 2003b;Hanson et al 2008;Siepker et al 2009). However, Philipp et al (1997) reported abandonment rates of 44% for catch-and-release smallmouth bass and largemouth bass, which were greater than rates for our study fish, albeit fish in both studies were removed from nests for similar periods.…”
Section: Discussioncontrasting
confidence: 80%
See 3 more Smart Citations
“…Catch-and-release fish were removed from the nest for a much shorter duration than tournament fish and did not experience the increased stress of weigh-in and displacement from nesting location. The abandonment rate of catch-and-release fish in our study (32%) was higher than that observed in similar studies with largemouth bass (about 10%; Siepker et al 2009) and smallmouth bass (0-10%; Suski et al 2003b;Hanson et al 2008;Siepker et al 2009). However, Philipp et al (1997) reported abandonment rates of 44% for catch-and-release smallmouth bass and largemouth bass, which were greater than rates for our study fish, albeit fish in both studies were removed from nests for similar periods.…”
Section: Discussioncontrasting
confidence: 80%
“…Climate, nest predators, condition of fish, and angling pressure can vary with latitude and may influence abandonment rates. Smallmouth bass exposed to tournament conditions in Missouri (similar latitudes to this study) had higher abandonment rates than two populations in Ontario (Hanson et al 2008). Similarly, catch-and-release angling abandonment rates of largemouth bass in our study (34%) were higher than rates for four lakes in Ontario (10%; Siepker et al 2009).…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…This approach allowed for a lakewide estimate of nest abandonment, as well as examination of variation in abandonment rate among transects given the spatial heterogeneity of crayfish. We began marking and tracking nests at the onset of spawning (when water temperature reached 15°C; Hanson et al, 2008). Initiation of spawning was highly synchronous, with a vast majority of nests beginning within the same 3-day period (19-21 May 2010).…”
Section: Methodsmentioning
confidence: 99%